Proposta para implantação de um sistema de transporte por bicicleta em um campus universitário - Morello, Deividy Paese (2018)
The growing increase in the use of vehicles and the problems generated either in the environment or by the difficulty of mobility in the urban space, has increased the interest about alternative modes of transportation, especially the use of the bicycle. Even with the inadequate infrastructure and the resistance of the users in relation to the comfort by the automobile there is urgency in the restructuring ofthe spaces with a view to sustainability. Thus, the present study presents a new possibility, of proposing for the implantation of a bicycle transport system, destined for university, in this case Campus I, of the University of Passo Fundo, seeking to contribute to a more sustainable urban mobility and that serves as a parameter for the implementation of bicycle lanes in other institutions. Therefore, we sought to verify the degree of interest of users in the implantation of bike path in the Campus, to define the design guidelines for the implantation of the bicycle path; apply guidelines in established sections of the course created and validate the project proposal through the opinion survey applied to Campus users. The methodology involved bibliographical research with analysis of previous studies, observations in loco, analysis of the legislation and municipal mobility plan, projection of the bike path and online opinion research. The project guidelines involved three main aspects involving the implantation of a bicycle system, the creation of bike stands and the promotion of bicycle use on campus. The project presents a route of 5,5 km, being possible three different stretches and each one with its specificities. 1.188 people participated, most of them undergraduate students, and the results showed that there is feasibility of implementation especially if aspects such as the provision of bicycle rental, construction of bathrooms and locker rooms, safety and improvement of public transport to the Campus. Important aspects of respondents with respect to layout should be considered in the implementation of the project, especially with regard to safety and lane size, as well as issues related to fewer incidents of barriers, crossings and stops along the bike path. It can be concluded that the proposal presented can serve as a model for other studies, providing a basis for other institutions to create or adapt their mobility systems with bicycle lanes, meeting users' expectations and the principles of sustainability.